The two-fold cost of sex: Experimental evidence from a natural system. Issue 1 (1st May 2017) - Gibson, Amanda K.; Delph, Lynda F.; Lively, Curtis M.
Abstract: Over four decades ago, John Maynard Smith showed that a mutation causing asexual reproduction should rapidly spread in a dioecious sexual population. His reasoning was that the per-capita birth rate of an asexual population would exceed that of a sexual population, because asexual females do not invest in sons. Hence, there is a cost of sexual reproduction that Maynard Smith called the "cost of males." Assuming all else is otherwise equal among sexual and asexual females, the cost is expected to be two-fold in outcrossing populations with separate sexes and equal sex ratios. Maynard Smith's model led to one of the most interesting questions in evolutionary biology: why is there sex? There are, however, no direct estimates of the proposed cost of sex. Here, we measured the increase in frequency of asexual snails in natural, mixed population of sexual and asexual snails in large outdoor mesocosms. We then extended Maynard Smith's model to predict the change in frequency of asexuals for any cost of sex and for any initial frequency of asexuals. Consistent with the "all-else equal" assumption, we found that the increase in frequency of asexual snails closely matched that predicted under a two-fold cost.